Paternal effects on fruit characteristics of some almond cultivars - Açar I.; Yilmaz A.; Ak B.E. (XVI GREMPA Meeting on Almonds and Pistachios, 2016)
The paternal effect in fruit trees is exhibited by differences among fruits borne on the same cultivar but developed from different source of pollen. The effect of pollinator on nut and kernel characteristics of almond was studied by measuring the nuts and kernels obtained from 12 crosses between self-incompatible and selfcompatible almond cultivars. Three domestic self-incompatible cultivars (‘Gulcan 1’, ‘Gulcan 2’ and ‘Akbadem’) were hand-pollinated with four male self-compatible cultivars: ‘Guara’, ‘Lauranne’, ‘Felisia’ and ‘Moncayo’. Quality characteristics were determined as nut weight (g), kernel weight (g), shelling percentage, double kernels, and nut and kernel dimensions (length, width and thickness). Nut and kernel characteristics showed differences according to the pollen sources.
16. Meeting of GREMPA (Groupe de Recherches Méditerranéennes pour l\'Amandier et Pistachier / Mediterranean Research Group for Almond and Pistachio), 2015/05/12-14, Meknes (Morocco)